Castings (Fundamental manufacturing processes, 2000)
Casting is the solidification of molten metal that is poured into a mold, or injected into a die having a cavity in the shape of the desired part. Casting is usually the quickest way to shape metal into a part, and is used both for prototyping and large quantity. This program covers an array of casting processes, arranging them into three major categories : expendable mold/reusable pattern processes, expendable mold/expendable pattern processes and permanent mold/no pattern processes. Pattern and core production methods are also demonstrated.